SMART Aqua system monitors water quality to produce quality crayfish - Nor Salwana, Mohammad Idris (2022)
PEKAN, 29 December 2021 - Redclaw crayfish Cherax quadricarinatus, also known as freshwater crayfish or lobster, is no stranger to seafood lovers to enjoy despite its high price in the market.